Was die Frauenbewegung erreicht hat - Freudenberg, Ika, 1858-1912 (Gerritsen collection of women's history, 1910)
A report on the progression and accomplishments of the women's movement. Topics range from reforms in law, education, and employment practices to changes in home and family life.